Position and Traumatic Lesion Localization in Cases of Motor Vehicle Accidents - Aydın, Berna; Biçer, Ümit; Çolak, Başar; Fincancı, Şebnem Korur (The Bulletin of Legal Medicine, 1998)
The present study was designed with the aim to evaluate the role of the localization of traumatic lesions in assessing the position in the motor vehicle as well as the relationship between position and traumatic lesion localization in cases of motor vehicle accidents with fatal and nonfatal outcome. In this framework 150 cases submitted to the Commissions and Traffic Department of the Council of Forensic Medicine in 1994 was evaluated. A considerable number of fatal outcomes in traffic accidents (31.2 %) were constituted of passengers followed by pedestrians with 21.3 % and drivers in 18 % of the cases. With regard to the distribution of severity and location of traumatic lesions in drivers and passengers of motor vehicles, the head (47.7 %) occupied the first place among cases with limited injuries, whereas this ratio dropped to 17 % in severe traumas. Minor injuries in drivers and passengers of open motor vehicles leading to nonfatal outcome were most frequently met in the head (35 %); severe injuries, on the other hand, involved preferentially (28.1 %) the lower extremities. No security belt was applied in 42 % of drivers and in 62 % of passengers. In cases of traffic accident related trauma and fatal outcomes, meticulous investigations for the assessment of location and severity of traumatic lesions and medico legal autopsies are inevitable. Mode of accident, extent of damages, as well as the question whether a security belt was used or not should be elucidated an identification of remnants found in the vehicle should be also undertaken. Key words: Traffic accident, Drivers-Passengers, Trauma, Autopsy